The primary application of indocyanine green fluorescence imaging in surgical oncology - Dai, Zhang-Yi; Shen, Cheng; Mi, Xing-Qi; Pu, Qiang (Frontiers in Surgery, 2023)
Background Indocyanine green (ICG) is a nontoxic, albumin-bound, liver-metabolized fluorescent iodide dye that has been widely utilized in clinical applications since the mid-1950s. However, after the 1970s, in-depth research on the fluorescence properties of ICG greatly expanded its application in the medical field. Methods In our mini-review, we searched the relevant literature on common oncology surgeries from PubMed, including lung cancer, breast cancer, gastric cancer, colorectal cancer, liver cancer, and pituitary tumors, using keywords such as indocyanine green, fluorescence imaging technology, and near-infrared fluorescence imaging. In addition, the application of targeted ICG photothermal technology in tumor therapy is briefly mentioned. Results In this mini-review, we analyzed studies on ICG fluorescence imaging in common surgical oncology and offered a thorough analysis of each form of cancer or tumor. Conclusion ICG has demonstrated significant potential in the detection and treatment of tumors in current clinical practice, although many applications are still in the preliminary stages, and multicenter studies are still required to more precisely define its indications, effectiveness, and safety.